Do regional house prices converge? Evidence from a major developing economy - Aytül Ganioğlu; Ünal Seven (Central Bank Review (CBR), 2021)
This paper analyzes the long-run convergence of regional house prices in a major developing country, Turkey. Using a non-linear time-varying factor model and quarterly hedonic house price data from 2010 to 2018, we find that house prices do not converge across 26 regions of Turkey. Results reveal that the regions can be grouped into seven convergence clubs and one divergent club, confirming the Turkish housing market's heterogeneity and complexity. We extend the analysis to explore the possible factors driving the convergence clubs. We find that income, population, education, unemployment, being in an earthquake zone, and inflow of Syrian refugees are significant driving forces in explaining convergence club formation. These outcomes will benefit home buyers/sellers, investors, regulators, and policymakers interested in analyzing the dynamic interlinkages among house prices and the effects of shocks originating from the regional housing markets in developing countries.
Keywords: R31; O18; C33; 330; Housing market; House prices; Log-t test; Regional convergence; Immobilienpreis; Räumliche Verteilung; Wohnungsmarkt; Türkei